A review of Pangasiid catfish genomics for conservation and aquaculture: current status and way forward - Abdul-Halim, Siti Amalia Aisyah; Esa, Yuzine; Duong, Thuy-Yen; Syukri, Fadhil; Rajandas, Heera; Parimannan, Sivachandran; Mohd-Nor, Siti Azizah (Universiti Putra Malaysia, 2024)
Due to its ecological and economic importance, the family Pangasiidae has been the focus of considerable biological and genetic research. This family includes thirty species of catfish distributed among four genera: Helicophagus, Pangasianodon, Pangasius, and Pseudolais within the order Siluriformes. In recent years, genomic-scale data for a wide range of aquatic species have been more easily available and accessible through next-generation sequencing. Draft genome sequences of numerous fishes have been the basis for many downstream investigations. However, although genomic-based technologies allow for the collection of robust data, there is a dearth of research on pangasiid catfishes, which could potentially enhance fisheries’ management and aquaculture. To realise its aquaculture potential and strategise the conservation of this family, fundamental knowledge of its biology, genetics, and genomics, among others, is critical. This review focuses on the current molecular knowledge of the family Pangasiidae, the remaining gaps, and the challenges faced in closing these gaps.